Children's (in)dependent mobility in Portugal. Issue 3 (May 2015) - Cordovil, R.; Lopes, F.; Neto, C.
Abstract Objectives To characterize children's independent mobility in Portugal, by studying the influence of age, sex, school type (primary/secondary) and location (urban/rural). To explore associations between mobility licences and children's actual independent mobility. Design Cross-sectional study of 1099 children between 8 and 15 years of age and their parents. Children attended primary (n = 660, 49% boys, 69% urban) and secondary (n = 439, 43% boys, 72% urban) schools. Methods The Portuguese version of the child independent mobility survey (Policy Studies Institute, London) was completed. Parents reported the mobility licences granted to their children. Children reported their independent mobility on school journeys and on weekends. Differences were examined in mobility licences and independent mobility by sex, urban/rural setting and primary/secondary schools. Multiple logistic regression models examined the associations between different variables and actual independent mobility. Results Secondary school children are granted more licences and have greater levels of independent mobility than primary school children. Only 21% of primary school children and 45% of secondary school children come home from school actively and independently. Overall, sex does not influence the licences granted to children in Portugal but boys have greater levels of independent mobility during the weekends than girls. Children in rural settings report engaging in more activities during the weekend. The number of mobility licences granted to the child was identified as predictor for actual independent mobility on school days and during the weekend. Conclusions Portuguese children lack independent mobility. Complementary qualitative research will be important to inform about the better practices to tackle this problem.